Growth and Characterization of cubic III-Nitrides by Molecular Beam Epitaxy - Zscherp, Mario Fabian; Justus Liebig University Giessen (My University, 2023)
The increasing performance demands for next-generation optoelectronics require materials which are capable of efficient light emission at high drive currents for all visible wavelengths. Cubic group III-nitrides are promising contenders to fulfill this task, because they lack internal polarization fields and promise to cover large parts of the electromagnetic spectrum. The ternary c-InxGa1-xN alloys are particularly interesting as their band gap can be tuned from the near-ultraviolet to the near-infrared. Their potential application in semiconductor devices demands the fabrication of high-quality thin films with smooth surfaces and low defect densities. However, the metastability of the cubic zincblende phase and the lack of suitable substrates limit the crystal quality of epitaxially grown c-III-nitrides. In addition, the growth of c-InxGa1-xN across the complete composition range has been deemed impossible due to an extensive miscibility gap for intermediate In contents. As a result, scientific publications investigating c-InxGa1-xN with In contents above 30% are scarce. The main contributions of this dissertation focus on improving the layer quality of cubic III-nitrides and enabling the growth of c-InxGa1-xN with any In content using plasma-assisted molecular-beam epitaxy. Publication 1 addresses the quality aspect by evaluating the impact of a c-AlN buffer layer on the growth of c-GaN on 3C-SiC. The buffer layer significantly improves the c-GaN layer quality and reduces defect density, surface roughness and hexagonal inclusions. Beyond the mere quality improvement, this is crucial for obtaining good c-GaN pseudo substrates for the subsequent growth of other III-nitrides. Subsequently, publication 2 achieves the growth of phase pure cubic InxGa1-xN over the entire composition range. The experimental results suggest that strain prevents the spinodal decomposition and reveal CuPt-like ordering for intermediate alloy compositions. Finally, it demonstrates light emission from the thin films ranging from ultraviolet to infrared and convincingly determines the emission energy as a function of composition. These results open up new research avenues towards materials properties of previous inaccessible compositions as well as towards device realization. This includes the fabrication of multi quantum well structures and the evaluation of their emission efficiency.
Wachstum und Charakterisierung kubischer III-Nitride mittels Molekularstrahlepitaxie
Keywords: Halbleiterphysik; Epitaxie; Materialwissenschaft; Charakterisierung; Nitride; ddc:530